(untitled) (Libellarium: journal for research in the field of information and related sciences, 2018)
The rapid development of information technology and persuasive use of Internet in every aspect of an individual’s life changed the way library users use libraries and what content and services they expect from their library website. Library users often complain that library websites are not user friendly and do not allow customers to find information they need by themselves due to the clutter of the content and technical jargon understood only by librarians. For a library website to meet the needs and expectations of its customers, it needs to be designed using User-Centred Design. Following this approach, this paper proposed a process necessary to understand the library users, benchmark other library websites, conduct user needs assessment, define content strategy, conduct task analysis, card sorting, prototyping, heuristic review and usability testing to ensure the website is designed with its customers in mind. The process described in this paper is based on author’s experience in the UX industry.